A Tribute to Géza Vermès : essays on Jewish and Christian literature and history - Vermès, Géza, 1924-2013; Davies, Philip R.; White, Richard T. (Journal for the study of the Old Testament. Supplement series, 1990)
This Festschrift honours one of today''s leading scholars of early Judaism and Christian origins. Twenty-two essays by internationally renowned scholars reflect the pioneering contribution of Geza Vermes in the fields of Dead Sea Scrolls, Targums and Rabbinics and New Testament.